Digitally enhanced assessment in virtual learning environments. (December 2015) - Pesare, Enrica; Roselli, Teresa; Rossano, Veronica; Di Bitonto, Pierpaolo
Abstract: One of the main challenges in teaching and learning activities is the assessment: it allows teachers and learners to improve the future activities on the basis of the previous ones. It allows a deep analysis and understanding of the whole learning process. This is particularly difficult in virtual learning environments where a general overview is not always available. In the latest years, Learning Analytics are becoming the most popular methods to analyze the data collected in the learning environments in order to support teachers and learners in the complex process of learning. If they are properly integrated in learning activities, indeed, they can supply useful information to adapt the activities on the basis of student's needs. In this context, the paper presents a solution for the digitally enhanced assessment. Two different Learning Dashboards have been designed in order to represent the most interesting Learning Analytics aiming at providing teachers and learners with easy understandable view of learning data in virtual learning environments.